2007
DOI: 10.1371/journal.pmed.0040334
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Retinitis: The Neglected Disease of the AIDS Pandemic

Abstract: The authors describe CMV retinitis in resource-poor settings and suggest possibilities for management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
144
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(152 citation statements)
references
References 42 publications
(44 reference statements)
7
144
0
1
Order By: Relevance
“…[2] A total of 1 815 patients were enrolled into the PEPFAR-funded CAPRISA AIDS Treatment Programme (CAT) at the eThekwini site in Durban, South Africa (SA) between June 2004 and August 2013. In this report, we highlight the three patients in this cohort who developed CMV retinitis.…”
Section: In Practicementioning
confidence: 99%
See 3 more Smart Citations
“…[2] A total of 1 815 patients were enrolled into the PEPFAR-funded CAPRISA AIDS Treatment Programme (CAT) at the eThekwini site in Durban, South Africa (SA) between June 2004 and August 2013. In this report, we highlight the three patients in this cohort who developed CMV retinitis.…”
Section: In Practicementioning
confidence: 99%
“…Data from Myanmar showed that 31% of the 42 patients diagnosed with CMV retinitis by fundoscopy, were asymptomatic. [2] Asymptomatic CMV retinitis was also demonstrated in 44% of Cambodian patients, despite the use of a questionnaire designed specifically to elicit symptoms of CMV retinitis.…”
Section: In Practicementioning
confidence: 99%
See 2 more Smart Citations
“…[53][54] Cytomegalovirus retinitis is strongly linked to mortality, commonly underdiagnosed, and rarely treated with needed systemic drugs. 71 A study from Myanmar reported that a third of patients diagnosed with cytomegalovirus retinitis on eye screening and given only local intraocular ganciclovir failed to survive 3 months. 72 Cotton wool spots, present in 15-50% of patients with low CD4 counts, [52][53][54] are strongly associated with high HIV viral load.…”
Section: Personal Viewmentioning
confidence: 99%